Physical insights into the grain size effect on the electrical properties of nanocrystalline La2Zr2O7 pyrochlores. Issue 7 (1st April 2023) - Kaliyaperumal, Chitrarasu; Marndi, Sundeep Kumar; Sankarakumar, Amirthapandian; Paramasivam, Thangadurai
Abstract: The role of grain size on the electrical properties of nanocrystalline La2 Zr2 O7 (LZO) ceramics prepared by chemical co-precipitation is reported. Grain size from 10 to 70 nm was obtained. The XRD and Raman scattering showed a pyrochlore structure of La2 Zr2 O7 . Morphology and chemical analysis were done by SEM and XPS, respectively. Electrical conductivity studies using impedance spectroscopy resolved the conductivity borne to grain and grain boundary with a non-Debye nature of conduction. The activation energy (Ea ) for electrical conduction through grain was almost the same for all the grain sizes and equal to 1.20 ± 0.03 eV. However, the Ea of the grain boundary had decreased from 1.17 eV to 0.78 eV with an increase in grain size, and the conduction is due to oxygen ion migration. The conduction mechanism was governed by the non-overlapping small polaron tunneling model. Additionally, ion-ion correlation in conduction is increased with increasing grain size. Graphical abstract: Image 1